PREVENTION AT PRESSURE SORES WITH REPOSITION HEALTH EDUCATION AND COCONUT OIL - Sunaryanti, Betty (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
The prevalence of pressure sores were reported in homes in the range of 12.9% to 19% (Potter and Perry., 2005). Suheri research results (2009) showed that the length of treatment in the occurrence of decubitus sores on immobilization patient 88.8% with an average on the fifth day of treatment. The results of Kurniawan research (2009) showed nurse knowledge of decubitus 66.7%, the purposes of prevention 59%, and the prevention of pressure sores 51.3%. So it is needed of a research in health centers community working area Karanganyar. The purpose of this research was to determine the effectiveness of the provision of reposition health education with coconut oil. This study was a quantitative study with Randomize Controlled Trial. Assessment of patients using the Norton scale assessment. The research was held for 7 days. There were four groups in this research, namely three treatment groups and one control group. The first treatment group received coconut oil in the region of the scapula, sacrum, and heels plus health education, the second treatment received coconut oil, while a third treatment received health education about repositioning, for the control group received standard preventive care. Statistical tests to determine the effectiveness of using a t-test. The results of the provision of reposition health education with coconut oil was effective for the prevention of pressure sores with p: 0.004. For referral results will be published through the Journal, made ââtextbook and seminar. Keywords: health education, coconut oil, decubitus